IMPROVING THE CREATIVE SKILL OF VOCATONAL HIGH SCHOOL STUDENTS THROUGH FLIPBOOK WITH AUGMENTED REALITY IN SOCIETY 5.0 - Hani Rahmiyanti; Sri Rahayu (LPPM Universitas Negeri Jakarta, 2025)
Society 5.0 has transformed education through digitalization and requires schools to develop students' creativity skills. Vocational schools play a major role in preparing students for change. The use of learning technology, especially virtual-based technology, is important to continue the developments. This study aims to measure the increase in students' creativity skills in vocational schools. The method used is a quasi-experiment to measure the increase in students' creative skills using control and experimental groups. The subjects in the quasi-experimental method were students in class X.3 and class X.4. The results of the study showed that the use of Flipbook learning media with Augmented Reality significantly improved the creative skills of vocational school students as seen from the increase in values in the Creative aspect in the experimental class showing a striking increase compared to the control class. In creative skills with a percentage of 91% for each experimental class, while the control class reached 70% each. These results indicate that the use of flipbooks with AR has succeeded in improving the creative skills of vocational high school students.